A Study on 3-Body Abrasive Wear Behaviour of Aluminium 8011 / Graphite Metal Matrix Composite. (September 2016) - Latha Shankar, B; Anil, K C; Patil, Rahul
Abstract: Metals and alloys have found their vital role in many applications like structural, corrosive, tribological, etc., in engineering environment. The alloys/composites having high strength to low weight ratio have gained attention of many researchers recently. In this work, graphite reinforced Aluminium 8011 metal matrix composite was prepared by conventional stir casting route, by varying the weight % of reinforcement. Uniform distribution of Graphite in matrix alloy was confirmed by optical micrographs. Prepared composite specimens were subjected to 3-body abrasive testing by varying applied load and time, the silica particles of 400 grit size were used as abrasive particles. It was observed that with the increase of weight% of Graphite the wear resistance of composite was also increasing and on comparison it was found that reinforced composite gives good wear resistance than base alloy.